Unique Sensitivity of Uterine Tissue and the Immune System for Endometriotic Lesion Formation - Morris, Stephanie A.; Korach, Kenneth S.; Burns, Katherine A. (Frontiers in Physiology, 2021)
Endometriosis is a debilitating disease that affects about 10% of reproductive aged adolescents and women. The etiology of disease is unknown; however, a prevailing hypothesis is that endometriosis develops from retrograde menstruation, where endometrial tissue and fluids flow back through the oviducts into the peritoneal cavity. There is no cure for endometriosis, and symptoms are treated palliatively. Despite the advances in knowledge, the complexity of endometriosis etiology is still unknown. Recent work by our group suggests the initiation of endometriosis is immune dependent. Using a mouse model of endometriosis, we hypothesized the initiation of endometriosis is immune regulated and uterine endometrium specific. In the absence of a functional immune system (NOD/SCID mice), endometriotic lesions did not form. When tissues having various levels of ESR1/ESR2, similar cellular composition to uterus (i.e. bladder, mammary gland, and lung), and treated with estradiol, only uterine endometrial tissue forms endometriotic lesions. Lesions derived from uterine endometrium expressed high levels of Mmp7 compared to the other non-uterine tissues. As MMP7 is known to play a major role in organization/re-organization of the endometrium during the menstrual cycle, blocking MMP activity significantly decreased the invasive properties of these cells. Together, these findings suggest endometriosis is immune and uterine specific and that MMP7 likely plays a role in the ability of uterine tissue and the innate immune system to establish and maintain endometriotic lesions.